Piano sonata no. 8 in C minor, op. 13 ("Pathètique") published by Simrock - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Bonn; N. Simrock; Germany)
Piano sonata no. 8 in C Minor, op. 13, variant issue of the Simrock edition with Pr. Fl. [blank] on title page